Financial econometrics : problems, models, and methods - Gourieroux, Christian, 1949-; Jasiak, Joann, 1963- (Princeton, N.J. : Princeton University Press, 2001)
"Financial econometrics is a great success story in economics. Econometrics uses data and statistical inference methods, together with structural and descriptive modeling, to address rigorous economic problems. Its development within the world of finance is quite recent and has been paralleled by a fast expansion of financial markets and an increasing variety and complexity of financial products. This has fueled the demand for people with advanced econometrics skills.".
"For professionals and advanced graduate students pursuing greater expertise in econometric modeling, this is a superb guide to the field's frontier. With the goal of providing information that is absolutely up-to-date - essential in today's rapidly evolving financial environment - Gourieroux and Jasiak focus on methods related to current research and those modeling techniques that seem relevant to future advances. They present a balanced synthesis of financial theory and statistical methodology.
Recognizing that any model is necessarily a simplified image of reality and that econometric methods must be adapted and applied on a case-by-case basis, the authors employ a wide variety of data sampled at frequencies ranging from intraday to monthly. These data comprise time series representing both the European and North American markets for stocks, bonds, and foreign currencies.
Practitioners are encouraged to keep a critical eye and are armed with graphical diagnostics to eradicate misspecification errors."--BOOK JACKET.
1. Introduction -- 2. Univariate Linear Models: The AR(1) Process and Its Extensions -- 3. Multivariate Linear Models: VARMA Representation -- 4. Simultaneity, Recursivity, and Causality Analysis -- 5. Persistence and Cointegration -- 6. Conditional Heteroscedasticity: Nonlinear Autoregressive Models, ARCH Models, Stochastic Volatility Models -- 7. Expectation and Present Value Models -- 8. Intertemporal Behavior and the Method of Moments -- 9. Dynamic Factor Models -- 10. Dynamic Qualitative Processes -- 11. Diffusion Models -- 12. Estimation of Diffusion Models -- 13. Econometrics of Derivatives -- 14. Dynamic Models for High-Frequency Data -- 15. Market Indexes -- 16. Management of Extreme Risks.
Includes bibliographical references (p. 451-476) and index.
Keywords: Econometrics; Finance -- Statistical methods; Finance -- Mathematical models